A mathematical model for steam-driven jet pump - Beithou, N; Aybar, HS (Pergamon-Elsevier Science Ltd, 2000)
There are several proposed advanced reactor systems that utilize steam-driven jet pump (SDJP) as an emergency core cooling system. The SDJP is a device without moving parts, in which steam is used as an energy source to pump cold water from a pressure much lower than the steam pressure to a pressure higher than the steam pressure. In this study, the mathematical modeling of the SDJP has been done under some assumptions for simplicity. An experimental analysis of the high pressure SDJP has been reported previously. The pressure profile of SDJP has been compared with Cattadori's experimental pressure profile. The discharge pressure in the experiment for the 8.7 MPa steam inlet pressure is given as 9.25 MPa which is 6.3% higher than the steam pressure. In the simulation, the discharge pressure is 9.58 MPa which is 10.1% higher than the steam inlet pressure. The comparisons show that the experimental and calculated pressure distributions are in good agreement in the mixing nozzle and diffuser, however, there are some difference in steam nozzle due to the assumptions made for steam nozzle. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: steam injector; jet pump; jet injector; condensing injector; ejector